Single-stream processing technique for in situ polymerization of glass fiber/polyamide-6 laminates. (December 2017) - Barfknecht, Peter W; Martin, Justin; Pillay, Brian; Vaidya, Uday K; Gray, Gary M
Ring-opening polymerization of anionic polyamide-6 (APA-6) requires both an activator and an initiator for the reaction to occur. Typical processing techniques for liquid-molded thermoplastic composite laminates involve infusion of the reinforcement with a premixed monomer solution containing both activator and initiator species. The technique described here is a step toward simplification and automation of the in situ polymerization process for composite laminates. By depositing the initiation functional group onto the reinforcement, infusion of a single stream of inert monomer solution is possible. The technique simplifies the processing equipment required and reduces the risk of contamination. Two separate methodologies derived from a silane and a diisocyanate were investigated. The soluble diisocyanate method was used to successfully demonstrate the single-stream APA-6 processing technique. Glass fiber surface-initiated polymerization was also demonstrated using the silane-derived initiator. The findings represent the first steps toward a new processing paradigm of APA-6 composites.